Physiological and Biochemical Changes of Vitro Propagated Bahana Plantlets Inoculated with Rhizobacteria and Agrobacteria - Ab. Rahman, Zuraida (2005)
A series of experiments were carried out to observe the effects of rhizobacterial and agrobacterial inoculation, singly or combined on the total content, concentration and distribution of the biochemical components (total soluble protein, soluble nitrogen, proline, peroxidase activity, total soluble phenolic, nitrate reductase activity, nitrate, chlorophyll), physiological characteristics (percentages of growth, number of roots, fresh and dry weight of roots, maximum and total length of roots) and mineral contents (N, P, K, Ca and Mg) of in vitro banana plantlets using MS (Murashige and Skoog, 1962) basal medium. The effects of rhizobacterial inoculation in modified MS medium containing sodium chloride (0.2%) and boron (1 yM and 10 pM) on the biochemical components, physiological characteristics and mineral content of the in vitro banana plantlets were also studied. Growth of banana plantlets cultured in modified MS liquid medium supplemented with different forms and concentrations of nitrogen or carbon sources and inoculated with Bacillus sphaericus UPMBl 0 was estimated. Results from the inoculation study using MS basal medium indicated that inoculation with rhizobacteria (Azospirillum brasilense Sp7, Bacillus sphaericus UPMBlO and Microbacterium oxydens UPMB11) or agrobacteria ( Agrobacterium rhizogenes strains AR9402 and A4) showed positive response on growth of in vitro banana plantlets compared to uninoculation after one month of culture. The inoculation treatment also increased the number of root, fresh and dry weight of roots and total length of root. At the same time, with inoculation the total content or concentration of the respective biochemical activity as total soluble protein, peroxidase, nitrate reductase, proline, nitrate, soluble nitrogen, phenolic and chlorophyll of the host plants increased and varied according to the type of bacteria used. Inoculation with these bacteria also enhanced the accumulation of N and P in the plantlets. Co-inoculation with rhizobacteria (Azospirillum brasilense Sp7, Bacillus sphaericus UPMB 1 0 and Microbacterium oxydens UPMB 1 1) and agrobacteria (Agrobacterium rhizogenes strains AR9402 and A4) also showed similar response as in single inoculation; UPMBlO+AR9402 treatment was the most effective treatment. The presence of rhizobacteria in the medium supplemented with 0.2% sodium chloride resulted in an improvement in growth and root biomass compared to the control (uninoculated). This rhizobacterial inoculation also produced an increase in protein, nitrate, soluble nitrogen and chlorophyll contents of the plantlets cultured in MS modified medium containing 0.2% sodium chloride. The descending order of effectiveness of the rhizobacteria in medium containing 0.2% sodium chloride was:UPMB 1 1 NPMB 1 O>Sp7. Similar response was shown when Bacillus sphericus UPMBlO was inoculated into medium containing boron at two concentrations: 1 pM and 10 pM. An increase in percentage of growth (> 295%) was shown when boron was applied into medium inoculated with Bacillus sphericus UPMB10. Results fiom the experiment of modified MS medium supplemented with different concentrations and forms of nitrogen also strongly indicated that inoculation with Bacillus sphericus UPMBlO has the potential to improve the in vitro plant growth especially in the absence of nitrogen. Inoculation with Bacillus sphericus UPME310 showed significant increased plant growth in treatment without nitrogen (- nitrogen) at 166% compared to un-inoculated only at 115%. Inoculation with Bacillus sphericus UPMBlO to enhance growth of in vitro plantlets could partly replace the expensive chemical nitrogen requirement for the plants. Bacillus sphericus UPMBlO seem to have the ability to increase growth of plantlets in medium supplemented with asparagine, potassium nitrate and urea. The descending order of effects of rhizobacterial inoculation on growth of plantlets varied according to the following N-sources in the MS modified media: asparagine (392%) > potassium nitrate (376%)> urea 291%. There was a negative response of Bacillus sphericus UPMBlO inoculation in promoting growth of plantlets in media containing KN03 (a range of 0 mM -300 mM) or (NH,+)2S04 (a range of 0 mM- 80mM) at all concentrations used. At 1.5% to 6.0% concentrations of sucrose, inoculated plantlets with Bacillus sphericus UPMBlO showed increased growth within a range of 250% to 304% compared to un-inoculated plantlets. It also indicate that inoculation with Bacillus sphaericus UPMBlO into the media containing carbon successfidly enhanced growth of in vitro plantlets. The descending order of effect of UPMBlO inoculation on plant growth varied according to the following carbon sources in the MS modified media: hctose (421%)> sucrose (356%)> glucose (354%)> maltose (221%)> sorbitol (78%)> rnannitol(51%). Therefore, inoculation with Bacillus sphaericus UPMBlO into the medium containing carbon sources produced positive response on the host plant, an effect which is dependent on the forms and concentrations of the carbon sources. The above finding provided evidence that Azospiriflum brasilense Sp7, BacilIus sphaericus UPMB 10, Microbacterium oxydens UPMBl 1, Agrobacterium rhizogenes strains AR9402 and A4, singly or combined are potentially effective in promoting growth of in vitro banana plantlets. Inoculation of rhizobacteria were showed beneficial to the plantlet in saline conditions through increment of growth and improvement in rooting system The effectiveness of inoculation is increased when associated with boron, nitrogen or carbon into the medium. Thus these bacterial strains could be used as a bioenhancer for growth of in vitro banana plantlets.